Of feathers and fur: Differential pollinator roles of birds and small mammals in the grassland succulent Aloe peglerae. (31st August 2016) - Payne, Stephanie L.; Symes, Craig T.; Witkowski, Ed T.F.
Abstract: The pollination syndrome of the genus Aloe, with gaudy inflorescences and orange–red flowers, suggests bird pollination. However, the diversity of flowering phenologies and structures suggests that generalizations within the group are currently uninformative because few studies have addressed the role of multiple pollinator guilds, especially mammals. Aloe peglerae, endemic to montane grassland of the Magaliesberg Mountains, South Africa, is primarily bird pollinated, although small mammals are recorded nocturnal visitors. We compared the independent contributions of diurnal and nocturnal visitors, i.e. birds and small mammals respectively, to reproductive success by assigning 12 flowering A. peglerae plants to each of four pollinator selective exclusion treatments: (i) no‐visitors; (ii) nocturnal‐visitors; (iii) diurnal‐visitors; and (iv) all‐visitors (control). Birds alone contributed more to fruit set (1.2–2.6 times), average seed/fruit (1.0–1.8 times) and total seed production (1.1–2.8 times) than both the all visitors (birds and small mammals combined) and the small mammal visitors respectively. The exclusion of all visitors resulted in no fruit set, suggesting that A. peglerae requires pollinators to set seed. Germination trials over six weeks and viability testing with tetrazolium staining identified no significant differences among the three treatments that produced fruit and seed. Germination success was 90–97%, indicating that seed quality of small‐mammal and bird‐pollinated plants are similar. Aloe peglerae inflorescences were visited continuously throughout the day and night, with the Cape rock‐thrush ( Monticola rupestris ) and dark‐capped bulbul ( Pycnonotus tricolor ) being the most abundant pollinators, accounting for 68.2% and 13.7% of all visits respectively in the control treatment. Small mammals, i.e. Namaqua rock mouse ( Micaelamys namaquensis ) and eastern rock sengi ( Elephantulus myurus ), while not increasing reproductive success in the absence of birds, are suitable alternative pollinators. The presence of diurnal bird and nocturnal small mammal visitors provides a diversity of pollinators in this resilient pollination syndrome.